The effect of different coating materials on the prevention of powder bounce in the next generation impactor - Shadi Farshbaf Khalili; Saeed Ghanbarzadeh; Ali Nokhodchi; Hamed Hamishehkar (Wolters Kluwer Medknow Publications, 2018)
In the process of quality control of pulmonary drug delivery products, aerosolization efficiency is mainly determined using impactors, e.g. next generation impactor (NGI). However, particle bounce may interfere with the validity and accuracy of results due to the overestimation of the respirable fraction. It is suggested that the coating of impactor's stages may prevent the particle bounce. Therefore, coating materials may influence the results of the aerosolization indexes of pulmonary dosage forms. The aim of this study was to investigate if the aerosolization indices are affected differently by using the different coating materials. In this study, the effects of using different materials including Span® 85, Tween® 80, silicon® oil, glycerin and Brij® 35/glycerin mixture recommended for the coating of NGI stages on the aerosolization indices such as fine particle fraction, fine particle dose, mass median aerodynamic diameter, and geometric standard deviation of salbutamol emitted from a commercial metered dose inhaler (MDI), were assessed. Three statistically different results were obtained on using Tween® 80, Span® 85 and silicon oil, and glycerin and Brij®35/glycerin mixture. It can be concluded that the type of coating material influenced the aerosolization indices of the examined MDI in NGIs.